2016
DOI: 10.1037/cdp0000031
|View full text |Cite
|
Sign up to set email alerts
|

“What are you?” Multiracial individuals’ responses to racial identification inquiries.

Abstract: A racial microaggression framework was relevant but not sufficient in reflecting the complex nature of racial identification inquiries for multiracial individuals. The insights into multiracial individuals' perceptions of these stimuli encourage more critical and dynamic thinking about racial categorization systems and interpersonal racial processes for this underrepresented but growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…In one study, more than 30% of bicultural Asian Americans reported being misperceived as foreign and/or a nonnative English speaker (Cheryan & Monin, 2005). Similarly, other studies showed 87% to 93% of biracial participants reporting experiences of identity denial or questioning (Townsend et al, 2009;Tran et al, 2016).…”
Section: Commonalities In Bicultural and Biracial Identity Challengesmentioning
confidence: 91%
“…In one study, more than 30% of bicultural Asian Americans reported being misperceived as foreign and/or a nonnative English speaker (Cheryan & Monin, 2005). Similarly, other studies showed 87% to 93% of biracial participants reporting experiences of identity denial or questioning (Townsend et al, 2009;Tran et al, 2016).…”
Section: Commonalities In Bicultural and Biracial Identity Challengesmentioning
confidence: 91%
“…While Nadal et al (2011) found that multiracial individuals reported experiencing microaggressions just as frequently as monoracial POC, they measured microaggressions using a scale developed for monoracial POC. Past work suggests that multiracial individuals may experience racial identity questioning and identity denial that a monoracial individual might not experience (Albuja, Sanchez, & Gaither, 2018;Johnston, & Nadal, 2010;Nadal et al, 2011;Shih & Sanchez, 2000;Tran, Miyake, Martinez-Morales, & Csizmadia, 2016).…”
Section: Experiences With Microaggressionsmentioning
confidence: 99%
“…While certainly not all multiracial individuals are racially ambiguous, many do share the common experience of being hard to categorize and are frequently asked "What are you?" (Tran, Miyake, Martinez-Morales, & Csizmadia, 2016). It may be precisely this ambiguity and difficulty in the categorization process that allows for malleability in social perception (i.e., different racial categorizations of the same target across varying situations and time).…”
Section: Perceiving Multiracial Targets: Malleability In Social Permentioning
confidence: 99%